NEW FINITE DEFORMATION MODEL FOR REINFORCED GRANULAR FILL OVER SUPER-SOFT RECLAIMED GROUND: I UNIFORMLY LOADED STRIP - K. Ramu; M. R. Madhav; H. B. Poorooshasb (International Association of Lowland Technology, 2008)
The presently available models for the analysis of reinforced foundation beds on soft ground are based on the infinitesimal deformation theory. A new model, which is extension and modification of Madhav & Poorooshasb (1988) model is proposed to estimate the settlement response of a uniformly loaded strip on reinforced granular fill laid over a super-soft reclaimed ground and to estimate the mobilized tension in the reinforcement considering the hyperbolic stress–displacement response of the super soft soil, hyperbolic shear stress–shear strain response of the granular fill and finite deformation theory. The proposed model also considers shear stresses mobilized on the top and the bottom surfaces of the geosynthetic layer and relates them to the respective normal stresses. Results indicate that the infinitesimal theory underpredicts the displacements compared to those from the finite deformation theory. Parametric studies carried out quantify the effects of each parameter on the settlements along the reinforced foundation bed and tension mobilized in the reinforcement and facilitates design of footings on reclaimed ground.